A comparative analysis of the microstructural and physicochemical properties of alluvial and dune sands from northeast Algerian Sahara - Rafika Hachem; Nassima Meftah; Ahmed Bouaziz (The Journal of Engineering and Exact Sciences)
This paper investigates the physical, chemical, and microstructural properties of two types of natural sand; alluvial sands and dune sand from the El-Oued region in the northeastern Algerian Sahara. Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), X-ray Fluorescence (XRF), Scanning electron microscopy (SEM/EDS), and granulometry analysis have been performed. The FTIR and XRD analysis prove that the alluvial sand and dune sand consist of high percentages of ?-quartz (SiO2), low amounts of calcite (CaCO3), and gypsum minerals (CaSO4;2H2O). The chemical analysis confirmed that both types of sand have a high silica (SiO2) ratio, reaching 80% for dune sand and 70% for alluvial sand, besides very low quantities of Al2O3, Fe2O3, and K2O oxides. CaO content was higher in alluvial sand than in dune sand. The shapes of alluvial sand grain samples ranged from angular to well-rounded. However, the dune sands have shapes ranging from sub-angular to well-rounded. However, the dune sand is poorly graded sand with a mean grain size of 250?m; whereas, the alluvial sand is well-graded sand with a mean grain size of 406?m. These findings demonstrate that alluvial and dune sands are mineralogically stable and chemically suitable for use as fine aggregates in construction. Also, these sands could be significant sources of quartz minerals.